'Just go away and do it and you get marks': the degradation of language teaching in neoliberal times. Issue 5 (3rd July 2016) - Block, David; Gray, John
ABSTRACT: The marketization of education in countries like the UK may be seen as part and parcel of the rise of neoliberalism as the dominant shaper of policy and practice in many societies from the late twentieth century onwards. This paper explores how marketization has impacted on two initial teacher preparation programmes and focuses on the Cambridge English Certificate in English Language Teaching to Adults (CELTA) as a particular kind of market driven model. It begins with a discussion of neoliberalism, marketization and the conditions of labour in neoliberal capitalism, making clear the complexity of these phenomena as well as the serious implications that they have for language teacher education. It then moves to a consideration of data from a specific CELTA course where some of these key issues can be seen to play out in ways which we suggest give cause for concern. Our conclusion is that programmes of this type both index and reinforce a model of English as purely instrumental and disembedded from social context and a model of professional activity which is highly instrumental and emblematic of the kind of deskilling and discrediting which have occurred in many professional sectors in recent decades.